Peningkatan Pemahaman Masyarakat Kelompok Nelayan Desa Pahlawan Tentang Konsep Dasar Perdagangan Internasional - Dewi Mahrani Rangkuty; Sanusi Ghazali Pane; Hartato Rianto; Miftahul Jannah (LPPM UMRI, 2021)
This community service activity aims to improve the understanding of the community of Pahlawan village fishermen as a service partner on the basic concept of international trade. The method of devotion is done by (1) observes; (2) counselling/socialization lectures; and (3) evaluation. The results of the devotion showed that the group of fishermen as participants/forums have shown enthusiasm in attendance, receiving information as an effort to add knowledge and insight from the method of counselling lectures/socialization of materials that have been conducted by the dedicated team. The team's recommendation for further community service activities after this stage is to perform the same methods with different themes such as differences in the number of fishermen's catches before and during the Covid-19 pandemic that can affect the export performance of fishery subsectors. To return to become additional information knowledge and insight in the community of the Pahlawan village fishermen group.